Велярный умлаут в древнеанглийском языке - Забулене, Л. (Kalbotyra, 1979)
Back mutation as a process of diphthongization depended both on the character of the root vowel and the consonant that followed it.The change was carried out more fully in non-West Saxon than in West Saxon where it generally took place only before liquid and labial consonants.In spite of the fact that after the change the sphere of distribution of the short diphthongs /ĕa/ /ĕo/ /ĭo/ became wider, the effect of back mutation on the morphological level of the language was of little consequence.